Wyobraźnia wzrokowa Paula Celana - das Aug, dunkel - Nowakowski, Grzegorz (Przestrzenie Teorii, 2007)
The article "The Visual Imagination of Paul Celan - das Aug, dunkel" raises the problem of the poet's search for language and "the place, from where you can see the best perspective". It shows the number of methodological dilemmas which inevitably result from analysing the visual imagination. It speaks of "the eye" understood as the crucial element of Celan's poetics. The author questions in his article the common percepcion of Celan as a poet of Shoah (as if) shifting the momentum to the eye. The eye, reduced in the very grammatical form of the word (Auge is turned into Aug), gives the unity to Celan's work. The eye, the restless wanderer, accompanies this poetry from the first to the last poem. The author of the article ventures to elucidate various aspects of the use of the organ of vision in Celan's poetry and draws a conclusion that the consistent theory of visual perception is central to Celan's work.